Does “The Purchasing Managers’ index” (PMI) affect the operational efficiency of commercial banks in Vietnam? - Oanh, Dao Le Kieu; Dan, Do The (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
This study investigates the impact of the Purchasing Managers’ Index (PMI) on the operational efficiency of 17 commercial banks in Vietnam from 2013 to 2020. Utilizing the Generalized Method of Moments (GMM), the research analyzes how macroeconomic factors such as GDP growth and inflation, alongside internal bank metrics, influence bank performance. The findings reveal an inverse relationship between PMI and bank operational efficiency. Additionally, GDP growth and inflation positively affect ROE, while non-performing loans negatively impact it. These results provide valuable insights for bank managers to enhance bank performance by monitoring the PMI.